Exploring Local Cultural Values in Career Instrument Development: Understanding Indonesian People’s Career Choice - Boby Ardhian Nusantara; Sinta Saraswati (Universitas Negeri Semarang, 2024)
Career Value has been studied in Indonesia in general in both psychology and career counseling for the past two years. However, none of these articles focus on the adaptation and validation of measurements carried out based on the guidelines for adapting measuring instruments, so that the measurements carried out are independent between one researcher and another. The use of instruments in different cultural backgrounds requires an adaptation process so that the measurement results are valid and reliable. The purpose of this study was to obtain a standardized Indonesian version of a career value measurement instrument. The adaptation process was carried out using an adaptation reference. Based on the results of the CFA analysis, it can be concluded that according to theory, the career value model consists of eight dimensions, namely social, management, specialization, mobility, independence, salary, team-work-balance, variety has a good fit model. This means that the null hypothesis stating that the career value goodness of fit model can be accepted. This explains that the resulting model can describe actual conditions.